SURGICAL TREATMENT OF LUNG CANCER COMPLICATED BY PLEURAL EFFUSION - N. A. Yaitsky; A. L. Akopov; R. . Makhmud; V. I. Egorov; I. V. Dejneka; I. V. Chistyakov (Вестник хирургии имени И.И. Грекова)
The authors made a retrospective analysis of 51 patients with non-small-cell lung cancer with pleural effusion, not associated with tumor lesion of pleural leaves. Out of 51operated patients 45 (88%) proved to be resectable. Among 45 patients (20 pneumonectomies, 24 lobectomies and 1 bilobectomy) combined interventions were fulfilled in 15 patients. In 27 (60%) out of 45 patients there was an injury of mediastinal lymph nodes, in 13 (29%) — intrapulmonary and root nodes. Complicated course of the postoperative period was noted in 27% of patients, lethality was 2%. One year survival after resection was 86%, three and five year survival was 54% and 30% respectively. The indices of survival reliably depended on the degree of lymphogenic dissemination. The presence of pleural effusion can not be a reason for refusal to fulfill radical surgical intervention.